2018
DOI: 10.1111/auar.12256
|View full text |Cite
|
Sign up to set email alerts
|

Accounting and Finance Graduate Employment Outcomes: Underemployment, Self‐employment and Managing Diversity

Abstract: The employment landscape for new graduates is increasingly challenging due to rapid changes in automation and globalisation, coupled with softening labour markets arising from economic uncertainty. For accounting and finance, there is the added complexity of a shift away from traditional core responsibilities and evidence of marginalisation among certain groups within the professions. The study used national data (N = 40 141) to examine the employment outcomes of accounting and finance graduates in Australia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 48 publications
(62 reference statements)
0
15
0
Order By: Relevance
“…A recent International Labour Organization report (2020) indicated that young people (aged 15–24) are three times more likely to be unemployed or underemployed than their adult counterparts. Graduates of Accounting and Finance courses in Australia are no exception with many working fewer hours than they wish and/or in roles that do not utilise the skills and knowledge acquired in their degree (Jackson, 2020a). To address this situation, universities are now putting greater emphasis on augmenting graduates' capacity to take ownership of their own careers to ensure both greater career sustainability (De Vos et al ., 2020) and opportunities for development.…”
Section: Introductionmentioning
confidence: 99%
“…A recent International Labour Organization report (2020) indicated that young people (aged 15–24) are three times more likely to be unemployed or underemployed than their adult counterparts. Graduates of Accounting and Finance courses in Australia are no exception with many working fewer hours than they wish and/or in roles that do not utilise the skills and knowledge acquired in their degree (Jackson, 2020a). To address this situation, universities are now putting greater emphasis on augmenting graduates' capacity to take ownership of their own careers to ensure both greater career sustainability (De Vos et al ., 2020) and opportunities for development.…”
Section: Introductionmentioning
confidence: 99%
“…One study on 28 lowincome Asian nations found that only about 13% of university graduates were considered to have the requisite skills and competencies that are required for their jobs (P. Brown et al 2011;Verma et al 2018). A survey of employment outcome of over 40,000 accounting and finance graduates in Australia found that only about 55% were in graduate-level jobs, with many graduates in short-term, casual, or part-time work (Jackson 2018;Bennett et al 2020). In 2015, about 30% of new business graduates in Australia were still unemployed four months after their graduation (Graduate Careers Australia 2015, as in, McArthur et al 2017.…”
Section: Empirical Studiesmentioning
confidence: 99%
“…Due to limited precedent set for the financial accounting of cryptocurrencies and related revenue recognition, no official guidance has yet been provided by the Financial Accounting Standards Board or the Securities and Exchange Commission (SEC); thus, it is unclear how companies may in the future be required to account for cryptocurrency transactions and assets and related revenue recognition. A recent paper by Jackson and Luu (2023) suggests some definitions and guidelines for accounting digital assets. Nevertheless, the paper falls short of fully addressing the main concerns raised in the EFRAG DP.…”
Section: An Introduction To Cryptoassetsmentioning
confidence: 99%